Institutions and Bank Performance: A Stochastic Frontier Analysis*. (4th November 2012) - Lensink, Robert; Meesters, Aljar
Abstract This article investigates the impact of institutions on bank efficiency and technology, using a stochastic frontier analysis of a data set of 7, 959 banks across 136 countries over 10 years. The results confirm the importance of well‐developed institutions for the efficient operation of commercial banks. Furthermore, the insights reveal the impact of institutional reforms in improving bank efficiency. The results are robust to adjustments in country‐specific effects, achieved by including country dummies, as well as across different risk profiles. Moreover, they provide empirical evidence in support of the public view of the banking sector.